2021
DOI: 10.54112/bcsrj.v2021i1.53
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Activities of Garlic Constituent Phytochemicals

Abstract: Garlic (Allium sativum L.) has medicinal value but also an important dietary component for centuries. It belongs to the family of Liliaceae, which is mostly grown and found in Ethiopia and Africa. Ethiopian garlic has been mostly used in traditional medicines. Inhibitory activity of garlic extract has been reported by various researchers for Lactobacillus acidophilus, Staphyloccocus aureus, Nocardia asteroids, pseudomonas aeruginosa, actinomyces viscosus, veillonella alcaligens bacterial strains. The garlic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 48 publications
(36 reference statements)
0
13
0
Order By: Relevance
“…Recent research has shown that the significant intake of phytochemicals protects the human body from different diseases (Iqbal et al, 2020; Kamalarajan, Muthuraman, Ganesh, & Valan, 2019). Different types of phytochemicals have been reported showing antimicrobial activity but still, their therapeutic potential has not been well‐studied (Ashfaq et al, 2021). Initial phytochemical screening of P. groenlandica extracts shows the presence of alkaloids, flavonoids, phenols and carbohydrates in all the six PGM, PGE, PGC, PGA, PGH and PGQ extracts.…”
Section: Resultsmentioning
confidence: 99%
“…Recent research has shown that the significant intake of phytochemicals protects the human body from different diseases (Iqbal et al, 2020; Kamalarajan, Muthuraman, Ganesh, & Valan, 2019). Different types of phytochemicals have been reported showing antimicrobial activity but still, their therapeutic potential has not been well‐studied (Ashfaq et al, 2021). Initial phytochemical screening of P. groenlandica extracts shows the presence of alkaloids, flavonoids, phenols and carbohydrates in all the six PGM, PGE, PGC, PGA, PGH and PGQ extracts.…”
Section: Resultsmentioning
confidence: 99%
“…An important component of C. paradisi is vitamin C. It is an essential micronutrient for humans, with pleiotropic functions related to its ability to donate electrons and a potent antioxidant and a cofactor for a family of biosynthetic and gene regulatory enzymes. Vitamin C contributes to immune defense by supporting various cellular functions of both the innate and adaptive immune system (Traber and Stevens, 2011;Ashfaq et al, 2021). It supports epithelial barrier function against pathogens and promotes the oxidant scavenging activity of the skin, thereby potentially protecting against environmental oxidative stress.…”
Section: Molisch's Testmentioning
confidence: 99%
“…8 Ethiopia has a long history of traditional medicine practice with about 80% of the population depending on traditional medicinal practices to safeguard their lives from various diseases. 9 From the medicinal herbs available in Ethiopia; 10 , 11 Allium cepa, Allium sativum, Nigella sativum, Brassica juncea, Zingiber officinale, Curcuma longa and Capsicum annum are mentioned in different literature for their antiviral activities ( Table 1 ). Inspired by previous experiences, herbal remedies are being considered as one of the alternative approaches in the treatment of COVID-19.…”
Section: Introductionmentioning
confidence: 99%